2021
DOI: 10.1016/j.jiac.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COVID-19 disease between young and elderly patients: Hidden viral shedding of COVID-19

Abstract: Objectives The symptoms of Coronavirus disease 2019 (COVID-19) vary among patients. The aim of this study was to investigate the clinical manifestation and disease duration in young versus elderly patients. Methods We retrospectively analyzed 187 patients (87 elderly and 100 young patients) with confirmed COVID-19. The clinical characteristics and chest computed tomography (CT) extent as defined by a score were compared between the two groups. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 18 publications
6
47
0
Order By: Relevance
“…received no or negative RT-qPCR nasal swabs and a positive Ab test) occur more frequent in residents than in staff members. This is in line with recent observations by Mori et al [3], who noted three times as many asymptomatic cases in older people (60 years and over) than in young people (18 -60 years old) with a confirmed SARS-CoV-2 infection. This is corroborated by the symptom data, as residents systematically reported fewer symptoms than staff members in PICOV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…received no or negative RT-qPCR nasal swabs and a positive Ab test) occur more frequent in residents than in staff members. This is in line with recent observations by Mori et al [3], who noted three times as many asymptomatic cases in older people (60 years and over) than in young people (18 -60 years old) with a confirmed SARS-CoV-2 infection. This is corroborated by the symptom data, as residents systematically reported fewer symptoms than staff members in PICOV.…”
Section: Discussionsupporting
confidence: 93%
“…The causative agent was named 'severe acute respiratory syndrome coronavirus 2' (SARS-CoV-2) and is closely related to SARS-CoV, which led to an epidemic between 2002 and 2004 [1]. It is estimated that around 40-45% of all SARS-CoV-2 infections remain asymptomatic [2], for which an dependency on age was observed [3]. Those who do develop COVID-19 present variable clinical out-comes, ranging from mild disease with typical symptoms including fever and cough to severe respiratory illness and death [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings brought information about individuals, who lived across 27 states of the country, which together cover 8,516,000 km 2 ( IBGE, 2020 ). The results were consistent with a systematic review and meta-analysis study, which showed that the higher the prevalence of comorbidities, the greater the chance of patients with COVID-19 needing intensive care ( Espinosa et al, 2020 ), especially if the pre-existing disease is hypertension, heart disease, Diabetes mellitus ( Du et al, 2020 ; Altunok et al, 2020 ), or chronic obstructive pulmonary disease ( Mori et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…Age related decreases in respiratory function have the potential to account for high incidence of respiratory symptoms among the elderly 43 . However, chest computer tomography did not show increased lung damage in elderly despite increased disease severity 44 , suggesting that lung aging by itself may not be the determining factor of severe COVID-19. Consistent with that, severity was associated with damage to other organs, mainly heart, liver and kidneys 35 .…”
Section: Introduction: Sars-cov-2 Virus and Covid-19 Infectionmentioning
confidence: 81%